Improvement of exercise tests and reduction of heart failure biomarkers in short term follow up after comprehensive rehabilitation program of patients with implanted LVAD. (14th October 2021) - Chwyczko, T; Smolis-Bak, E; Zalucka, L; Segiet-Swiecicka, A; Piotrowicz, E; Was, J; Niedolistek, M; Kowalik, I; Furmanek, M; Sobieszczanska-Malek, M; Zielinski, T; Szymanski, J; et al.
Abstract: Background: There is increasing recognition of the importance of rehabilitating patients after LVAD implantation. The novel method of comprehensive rehabilitation starting directly after LVAD implantation was designed for our LVAD patients population. Aim of the study: The study aimed to determine, if novel rehabilitation program improves functional and biochemical parameters in patients after recent LVAD implantation. Study group: 37 recent LVAD (22 Heart Mate III, 15 HeartWare) recipients (19–67, mean 58.7 years, 35 men) participated in specially designed rehabilitation program. The program included 4–5 weeks of sationary rehabilitation: supervised endurance training on cycloergometer (5 times per week), resistance training, general fitness exercises with elements of equivalent and coordination exercises (every day). It was followed by individual exercises performed at home. At the beginning and at the end of rehabilitation program the patients performed 6 minute walking test (6MWT), cardiopulmonary exercise test (CPET). Following prognostic biomarkers of heart failure: NT-proBNP, galectin-3 and ST2 were also measured. Results: See table 1. Increase of 6MWT distance, higher maximal workload, peak VO2 and upward shift of anaerobic threshold in CPET were observed in all patients. Significant reductions of NTproBNP, ST2 and galectin-3 levels were observed. There were no major adverse events during rehabilitation. Conclusions: Comprehensive novel rehabilitation in LVAD recipients is safe and results in significant improvement of functional tests and biomarkers of heart failure. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Center for Research and Development: National grant - STRATEGMED II,